TROPHY registry — status report - Thomale, U. W.; Auer, C.; Spennato, P.; Schaumann, A.; Behrens, P.; Gorelyshev, S.; Bogoslovskaia, E.; Shulaev, A.; Kabanian, A.; Seliverstov, A.; Alexeev, A.; Ozgural, O.; et al. (Childs Nervous System, 2021)
Introduction: The TROPHY registry has been established to conduct an international multicenter prospective data collection on the surgical management of neonatal intraventricular hemorrhage (IVH)-related hydrocephalus to possibly contribute to future guidelines. The registry allows comparing the techniques established to treat hydrocephalus, such as external ventricular drainage (EVD), ventricular access device (VAD), ventricular subgaleal shunt (VSGS), and neuroendoscopic lavage (NEL). This first status report of the registry presents the results of the standard of care survey of participating centers assessed upon online registration. Methods: On the standard of treatment forms, each center indicated the institutional protocol of interventions performed for neonatal post-hemorrhagic hydrocephalus (nPHH) for a time period of 2 years (Y1 and Y2) before starting the active participation in the registry. In addition, the amount of patients enrolled so far and allocated to a treatment approach are reported. Results: According to the standard of treatment forms completed by 56 registered centers, fewer EVDs (Y1 55% Y2 46%) were used while more centers have implemented NEL (Y1 39%; Y2 52%) to treat nPHH. VAD (Y1 66%; Y2 66%) and VSGS (Y1 42%; Y2 41%) were used at a consistent rate during the 2 years. The majority of the centers used at least two different techniques to treat nPHH (43%), while 27% used only one technique, 21% used three, and 7% used even four different techniques. Patient data of 110 infants treated surgically between 9/2018 and 2/2021 (13% EVD, 15% VAD, 30% VSGS, and 43% NEL) were contributed by 29 centers. Conclusions: Our results emphasize the varying strategies used for the treatment of nPHH. The international TROPHY registry has entered into a phase of growing patient recruitment. Further evaluation will be performed and published according to the registry protocol.
CRIS-Team Scopus Importer:2023-12-20
Keywords: External ventricular drainage; Infant hydrocephalus; Neuroendoscopic shunt; Posthemorrhagic hydrocephalus; Subgaleal shunt; TROPHY; Ventricular access device